APLIKASI ENKRIPSI CITRA MENGGUNAKAN ALGORITMA KRIPTOGRAFI ARNOLD CAT MAP Dan LOGISTIC MAP - Pahrul Irfan (Universitas Bumigora, 2016)
Data security in the process of information exchange is very important. One way to secure the image is to use cryptographic techniques. Cryptographic algorithms applied to the image is used to randomize the position of pixels using a secret key parameters, so that images can not be recognized anymore after the encryption process. In this study, researchers used the algorithm of chaos known as algorithms compact, fast and commonly used in cryptography especially those in the image file. The results showed the image that has been through an encryption process can not be recognized because the randomization process image pixel position is performed using chaos algorithm.